Multi-tier approaches to the resolution of international disputes : a global and comparative study - Reyes, Anselmo; Gu, Weixia (Cambridge : Cambridge University Press, 2022)
Multi-tier dispute resolution (MDR) entails an early attempt at mediation followed by arbitration or litigation if mediation is unsuccessful. Seemingly, everyone acknowledges MDR's attractiveness as a means of resolving disputes due to its combination of the flexibility and informality of mediation with the rigour and formality of arbitration or litigation. Yet, the question is why, except in China and some Asian jurisdictions, MDR is not resorted to around the world and MDR clauses in commercial contracts remain relatively uncommon. This book responds to that question by (1) surveying global regulatory approaches frameworks for MDR, (2) comparing MDR trends in Asia and the wider world, (3) identifying MDR's strengths and weaknesses, and (4) prescribing ways to address MDR's weaknesses (the enforceability of MDR clauses, the difficulties arising when the same person acts as mediator and decision-maker in the same dispute, and the enforcement of mediated settlement agreements resulting from MDR).
Mapping and assessing the rise of multi-tiered approaches to the resolution of international disputes across the globe : an introduction / Weixia Gu -- A snapshot of national legislation on same neutral med-arb and arb-med around the globe / Hiro N Aragaki -- Combinations of mediation and arbitration : the case of China / Weixia Gu -- The resolution of international commercial and financial disputes : hybrid dispute resolution in Hong Kong / Julien Chaisse and Carrie Shu Shang -- Multi-tier dispute resolution : present situation and future developments in Taiwan / Kuan-Ling Shen -- Perspectives and challenges of multi-tier dispute resolution in Japan / Yuko Nishitani -- Might there be a future for multi-tiered dispute resolution in Korea? challenges and prospects / Joongi Kim --Combinations of mediation and arbitration : the Singapore perspective / Man Yip B. -- HKIAC's experience of the use of multi-tier dispute resolution clauses / Sarah Grimmer -- The use of conciliation and litigation by the Hong Kong Equal Opportunities Commission (EOC) / Anselmo Reyes and Wilson Lui -- Multi-tier commercial dispute resolution processes in the United States / Thomas J Stipanowich -- Multi-tiered dispute resolution clauses : an English perspective / Eva Lein -- Multi-tier and mixed-method dispute resolution in Canada : from obscurity to prominence in a single generation / Joshua Karton and Michelle de Haas -- Multi-tier dispute resolution in Australia : a tale of 'Escalating' acceptance / Richard Garnett -- Praised, but not practised : the EU's paradoxes of hybrid dispute resolution / Julien Chaisse -- Multi-tier dispute resolution in Russia / Alexander Molotnikov -- Multi-tier dispute resolution under OHADA law / Justin Monsenepwo -- Making multi-tier dispute resolution work / Anselmo Reyes.
Title from publisher's bibliographic system (viewed on 09 Dec 2021).
Keywords: Dispute resolution (Law); International commercial arbitration; Arbitration (International law)